The Semantics of Yojijukugo Containing the Kanji for 'Tiger' in Yojijukugo no Hakkajiten - Isnaedah Hanum; Ana Natalia (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
This study aims to reveal the denotative and connotative meanings of yojijukugo containing the kanji "tiger" (虎) using a semantic approach. The data were collected from the website Yojijukugo no Hakkajiten, an online encyclopedia containing thousands of four-kanji idioms (yojijukugo). This research employs a qualitative descriptive method, analyzing linguistic and cultural meanings based on lexical and symbolic interpretations. The findings show that yojijukugo involving the tiger kanji carry various meanings depending on their context. Of the 30 yojijukugo analyzed, the denotative meaning reflects literal combinations of kanji, meanwhile, connotative meaning is associated with the personal emotions or thoughts of the speaker and the interlocutor. Yojijukugo such as 為虎添翼 (enhancing the strong) and 虎穴虎子 (valor in risk-taking) hold positive connotations, in contrast 苛政猛虎 (oppressive government is worse than a tiger) and 虎頭蛇尾 (strong start, weak finish) convey negative connotations. These findings affirm that tiger-based yojijukugo are not merely linguistic expressions, but also deep representations of Japanese cultural values.